Evaluation of STEM Education Programs (Science, Technology, Engineering, Mathematics) in Increasing Students' Interest in Learning - Ningsi, Weni Indria (Lembaga Riset Mutiara Akbar, 2023)
STEM (Science, Technology, Engineering, and Mathematics) is an education system that can develop students' ability to solve problems, be more innovative, independent, and can connect what they learn at school with real life. Good innovation is when students are able to connect all aspects of STEM and combine four inter-disciplinary aspects of STEM so that they can solve a problem. The four STEM disciplines that have been described by Torlakson (2014) are: (a) Science, which is the science of nature, which represents natural laws related to physics, chemistry and biology and the treatment or application of related facts, principles, concepts and convections. with these scientific disciplines. (b) Technology, is a skill or a system used in managing society, organizations, knowledge or can be defined as a product of science and engineering. (c) Engineering, is engineering knowledge by utilizing concepts from science and mathematics as well as technological tools to solve a problem. (d) Mathematics, is knowledge that connects quantities, space and numbers which requires logical arguments.